Ordering And Customizing Cake System (Dec-O-Cake) / Nur Farhin Jailani - Jailani, Nur Farhin (2014)
People nowadays become easily attracted to an e-commerce site that fancy and trendy. A lot of today’s e-commerce sites apply customizing method. Today, having a cake in most occasions becoming a trend. However, ordering and purchasing a cake manually took a lot of processes and it is time consuming. The other problem that might exist is cakes offered in bakery shop usually limited to ready-made cake only which usually does not suit customer’s desire. Problem of the customer cannot view their sample (image) of their customized-cake also matter the most since this situation may influences the tendency of not buying any product at all. In order to solve these problems, Dec-O-Cake has been developed to the target user. The target user is for anybody who wants to purchase a cake and for those who are seeking for a new idea in decorating a cake with an in-trend decorations. To achieve the target objectives, Waterfall Model is used in the development of Dec-O-Cake. Important phases including Requirements, Design, Implementation, Testing and Maintenance are carefully followed in order to develop high-quality system. This system is finally be tested to thirty respected respondents which also acts as real user. Questionnaires made up from three different sections which are ‘User Interface’, ‘Functionability’ and ‘Ease of Use’ respectively. The questionnaire then are distributed and Linkert Scale is used to easily rate the level of agreeable from 1-5 which indicates strongly agree, disagree, neutral, agree and strongly agree. Most of the respondents had agreed that Dec-O-Cake would bring such a significant benefit and solve their problems.